A comprehensive review on bio-inspired flower pollination algorithm. Issue 5 (4th July 2022) - Mohanty, Smita; Dash, Rajashree
Abstract: Since time immemorial, the complex and highly nonlinear nature of various optimization problems in science and engineering has motivated researchers to develop sophisticated solutions. Along with traditional algorithms, in recent years, many computationally intelligent meta-heuristic techniques have also grabbed attention due to their effectiveness and flexibility. Flower Pollination Algorithm (FPA) is one such biologically-motivated procedure, which is influenced by the fertilization procedure of flowering species of plants. It has been effectively incorporated to fix many real-world problems in fields like wireless sensor networking, signal processing, power and communications, rain fall prediction, global function optimization and many more. Keeping in mind, its growing popularity due to its simplicity, adaptability and cross domain applicability, in this paper, a comprehensive review on FPA is presented. It throws light on its biological inspiration, algorithm, variants and applications in various industries.